2012
DOI: 10.18637/jss.v048.c01
|View full text |Cite
|
Sign up to set email alerts
|

IRTrees: Tree-Based Item Response Models of the GLMM Family

Abstract: A category of item response models is presented with two defining features: they all (i) have a tree representation, and (ii) are members of the family of generalized linear mixed models (GLMM). Because the models are based on trees, they are denoted as IRTree models. The GLMM nature of the models implies that they can all be estimated with the glmer function of the lme4 package in R. The aim of the article is to present four subcategories of models, the first two of which are based on a tree representation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
243
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(259 citation statements)
references
References 47 publications
1
243
0
Order By: Relevance
“…They dichotomized each individual's response times (from a verbal analogies and a progressive matrices test) into a fast vs. slow category, based either on the person's median or on the median response time to each item, yielding fast-correct, fast-incorrect, slow-correct, and slow-incorrect response categories. They then fit a 1PL IRTree model [129], and found that three different latent traits were required to fit the data: speed, slow intelligence, and fast intelligence. They also found that although fast and slow intelligence were highly correlated, they were distinguishable.…”
Section: Fast Vs Slow Responding = Fast Vs Slow Thinking?mentioning
confidence: 99%
“…They dichotomized each individual's response times (from a verbal analogies and a progressive matrices test) into a fast vs. slow category, based either on the person's median or on the median response time to each item, yielding fast-correct, fast-incorrect, slow-correct, and slow-incorrect response categories. They then fit a 1PL IRTree model [129], and found that three different latent traits were required to fit the data: speed, slow intelligence, and fast intelligence. They also found that although fast and slow intelligence were highly correlated, they were distinguishable.…”
Section: Fast Vs Slow Responding = Fast Vs Slow Thinking?mentioning
confidence: 99%
“…In order to allow quantitative analysis of the categorical responses to the treatments, we analysed them using item response tree GLMMs [29]. This technique, borrowed from sociometrics, can be adapted and used as a way to handle categorical data of behaviour [30].…”
Section: (D) Statistical Analysismentioning
confidence: 99%
“…These prior approaches, however, have some limitations. For instance, the models proposed by De Boeck and Partchev (2012) do not allow for trees with more than two branches and rely on one-parameter logistic models, while Bockenholt (2012) is based on one-parameter probit models.…”
Section: Introductionmentioning
confidence: 99%